A study of year three and year four science education student teachers’ nature of science beliefs and their science teaching and learning beliefs - Ngwenya, N. H.; Imenda, S. N. (South African Journal of Higher Education, 2025)
The purpose of this study was to determine the nature of science (NOS) beliefs, science teaching and learning beliefs held by year-three and year-four science education student teachers, and how those beliefs related to each other. The study was underpinned by the epistemological development theory. Researchers conducted a quantitative study involving one hundred and eighty-four year-three and year-four students enrolled in a four-year Bachelor of Education degree. The study revealed that: (i) year-four student teachers held significantly more sophisticated NOS beliefs than year-three students; (ii) year-four science teaching and learning beliefs were significantly “reformed oriented” than year-three students, and (iii) no statistically significant correlation existed between the year-three respondents’ NOS beliefs as against their science teaching and learning beliefs. However, there was a statistically significant linear association between the students’ NOS beliefs and their science teaching and learning beliefs at year-four level.